Managing Human Potential in the AI Era for Financial Sustainability in MSMEs - Ardi Armen; Taufan Herjanto (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research aims to explore strategies for managing human potential amidst technological disruption, specifically focusing on ensuring financial sustainability in Micro, Small, and Medium Enterprises (MSMEs). The research adopts a qualitative approach, employing interviews and case studies to delve into the intricacies of the topic. Sampling techniques include purposive sampling to select MSMEs representative of diverse sectors and regions. Data analysis involves thematic analysis, identifying patterns and themes within the collected data. Preliminary findings underscore the significance of fostering a culture of adaptability, upskilling, and innovation within MSMEs to thrive in the AI era. Moreover, the research highlights the pivotal role of effective leadership and organizational support structures in maximizing human potential for sustainable business outcomes amidst technological disruptions.